A field study to describe diel, tidal and semilunar rhythms of larval release in an assemblage of tropical rocky shore crabs - Flores, Augusto A. V.; Mazzuco, Ana Carolina A.; Bueno, Marilia (Springer, 2007)
Available information on the larval release rhythms of brachyurans is biased to temperate estuarine species and outcomes resulting from some sort of artificial manipulation of ovigerous females. In this study we applied field methods to describe the larval release rhythms of an assemblage of tropical rocky shore crabs. Sampling the broods of ovigerous females of Pachygrapsus transversus at two different shores indicated a spatially consistent semilunar pattern, with larval release maxima around the full and new moon. Yet, synchronism between populations varied considerably, with the pattern obtained at the site exposed to a lower wave action far more apparent. Breeding cohorts at one of the sampled shores apparently belonged to actual age groups composing the ovigerous population. The data suggest that these breeding groups release their larvae in alternate syzygy periods, responding to a lunar cycle instead of the semilunar pattern observed for the whole population. For the description of shorter-term rhythms, temporal series at hour intervals were obtained by sampling the plankton and confinement boxes where ovigerous females were held. Unexpectedly, diurnal release activity prevailed over nocturnal hatching. Yet, only grapsids living higher on the shore exhibited strong preferences over the diel cycle, with P. transversus releasing their larvae during the day and Geograpsus lividus during the night. The pea crab Dissodactylus crinitichelis, the spider crab Epialtus brasiliensis and a suite of xanthoids undertook considerable releasing activity in both periods. Apart from the commensal pea crab D. crinitichelis, all other taxa revealed tide-related rhythms of larval release, with average estimates of the time of maximum hatching always around the time of high tides; usually during the flooding and slack, rather than the ebbing tide. Data obtained for P. transversus females held in confinement boxes indicated that early larval release is mostly due to nocturnal hatching, while zoeal release in diurnal groups took place at the time of high tide. Since nocturnal high tides at the study area occurred late, sometimes close to dusk, early release would allow more time for offshore transport of larvae when the action of potential predators is reduced.
Keywords: field methods; larval release; tropical rocky shores; Brachyura